Delineating Environmental Stresses to Primary Production of U.S. Forests From Tree Rings: Effects of Climate Seasonality, Soil, and Topography. Issue 2 (15th February 2020) - Dannenberg, Matthew P.; Song, Conghe; Wise, Erika K.; Pederson, Neil; Bishop, Daniel A.
Abstract: Primary production is the entry point of energy and carbon into ecosystems, but modeling responses of primary production to "environmental stress" (i.e., reductions of primary production from nonoptimal environmental conditions) remains a key challenge and source of uncertainty in our understanding of Earth's carbon cycle. Here we develop an approach for estimating annual "environmental stress" from tree rings based on the proportion of the optimal diameter growth rate (from species‐specific allometric equations) that is realized in a given year. We assessed climatic, topographic, and soil drivers of environmental stress, as well as their interactions, using both empirical model experiments and linear mixed effect models. Climate gradients and interannual climate variability dominated spatial and temporal variability of environmental stress in much of the western United States, where the tree‐ring environmental stress index was positively correlated with antecedent climatic water balance (precipitation minus potential evapotranspiration) and negatively correlated with temperature and vapor pressure deficit. Excluding topographic and soil information from empirical models reduced their ability to capture spatial gradients in environmental stress, particularly in the eastern United States, where growth was not as strongly limited by climate. Mean climate conditions and topographic characteristics had significant interaction effects with the climatic water balance, indicating an increasing importance of winter moisture for warmer and drier sites and as elevation and topographic wetness index increased. These results suggest that including effects of antecedent climate (particularly in dry regions) and site topographic and soil characteristics could improve parameterization of environmental stress effects in primary production models. Plain Language Summary: Carbohydrates produced through photosynthesis form the building blocks of ecosystems and provide many goods and services to humanity, including basic needs like food and shelter. The amount of carbohydrates produced by plants depends on favorable climate conditions and adequate supply of key resources, but it has always been challenging to predict precisely where, when, and how much plant activity will be reduced when environmental conditions are not optimal. We used tree‐ring widths from more than 1, 000 sites across the United States to examine which environmental conditions were responsible for reduction of plant growth below optimal levels. Importantly, we found that temperature, rainfall, and humidity before plants even start growing act as important constraints on growth. Rainfall and snowfall from the previous autumn through spring are particularly important for growth in dry regions like the western United States. However, the effects of climate on plant growth differ depending on the conditions in which plants are growing, such as their elevation and soil quality. Predicting how plants respond to their environment therefore depends not just on the weather they experience while they are growing but also on the legacies of previous weather and on the soil and topography conditions where they are growing. Key Points: We developed annual estimates of environmental stress (ratio of actual to optimal growth) from tree rings Lag effects of climate were important drivers of environmental stress in most ecoregions but especially in dry ecoregions Topography and soil quality affected both spatial gradients of environmental stress and relationships between climate and growth